2016
DOI: 10.1007/s11187-016-9758-1
|View full text |Cite
|
Sign up to set email alerts
|

Students climbing the entrepreneurial ladder: Does university internationalization pay off?

Abstract: The entrepreneurial university is emerging as a new archetype of higher education institution that fosters knowledge generation and transfer, contributes to local development and empowers individuals in fastchanging markets. Many institutional, strategic and organizational factors have been discussed as components or contingencies of the process that makes universities more entrepreneurial. Yet we miss an understanding of the contribution that internationalization, crucial strategy for university competitivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 93 publications
(141 reference statements)
0
34
0
8
Order By: Relevance
“…According to Minola et al (2016), several strategical and organizational issues have been discussed in the transformation process of making universities more entrepreneurial. However, the role of internationalization has been misunderstood in the academic debate of emerging universities models (Knight 2015).…”
Section: Students' Entrepreneurship Engagement and University Internamentioning
confidence: 99%
See 1 more Smart Citation
“…According to Minola et al (2016), several strategical and organizational issues have been discussed in the transformation process of making universities more entrepreneurial. However, the role of internationalization has been misunderstood in the academic debate of emerging universities models (Knight 2015).…”
Section: Students' Entrepreneurship Engagement and University Internamentioning
confidence: 99%
“…This issue plays a particular interest in the current socioeconomic scenario because the contribution of internationalization is crucial for the competitiveness of each type of organization (Knight 2004). Adopting the basis of internationalization theory and using a multilevel analysis with data from 25,855 students enrolled in 130 European Universities, Minola et al (2016) analyze the effect of university internationalization on students' progressive engagement in entrepreneurship, as well as, along the core entrepreneurial university missions (teaching, research, and socio-economic contribution). These authors found that the internationalization strategy has a positive direct effect on the European students' level of engagement in entrepreneurship, as well as, acts as a moderator of the relationship between entrepreneurial university' supports and the students' level of engagement in entrepreneurship.…”
Section: Students' Entrepreneurship Engagement and University Internamentioning
confidence: 99%
“…Since our sample is made up of individual-level observations, which are clustered within countries, we follow a multi-level mixed-effects regression approach (both random and fixed effects) (Rabe-Hesketh and Skrondal 2008). In EE, research multilevel estimation has been used for example by Walter and Dohse (2012) and Minola, Donina, and Meoli (2016) who collected individual level and regional/country level data to study EE and students' entrepreneurship.…”
Section: Estimation Techniquementioning
confidence: 99%
“…7. Like in the present article, Minola, Donina, and Meoli (2016) operationalize EE as the count of 14 different initiatives offered to students to investigate the effects on students' entrepreneurial behaviour. 8.…”
Section: Notesmentioning
confidence: 99%
“…As Daniels (2013) points out, drive for internationalization in higher education is not without its challenges and potential for conflict among a wide range of local and global stakeholders with divergent motivations and perspectives. Higher education institutes (HEIs) have assertive reasons to invest in internationalization activities as it can lead to attain higher earnings, goodwill and competitive advantages in global market (Minola, T., Donina, D., & Meoli, M., 2016).…”
Section: Introductionmentioning
confidence: 99%